BIOLOGY ASPECT OF MANGROVE SNAILS (Telescopium telescopium) AT LANTEBUNG MANGROVE ECOTOURISM MAKASSAR CITY - Mesalina Tri Hidayani; Hartati Tamti; Norasyikin Norasyikin (Universitas Mataram, 2024)
Mangrove snails (Telescopium telescopium) is one of the biota that plays a role in the process of litter decomposition and mineralization of organic matter in mangrove plants. The purpose of this study is to determine the abundance, size structure, growth pattern of mangrove snails (Telescopium telescopium) and water quality in the Lantebung Mangrove Ecotourism in Makassar City. The method of collecting mangrove snails by purposive sampling uses a quadrant transect measuring 1x1 m2 with three repetitions at three observation stations. The water quality parameters measured were temperature, salinity, pH, and sediment. The results showed that the abundance of mangrove snails was 45 individuals (Station I), 46 individuals (Station II), and 45 individuals (Station III) respectively. The length of the mangrove snail (Telescopium telescopium) of station I ranged from 55.5-78.1 mm, station II 52.9-72.6 mm and station III 55.3-77.1 mm. The weight structure of the mangrove snail (Telescopium telescopium) of station I ranged from 17.0-37.4 g, station II 17.0-30.3 and station III 17.0-41.0 g. The growth pattern of mangrove snails based on the weight length relationship at the three stations showed a negative allometric equation (b<3), i.e. the length increase was faster than the weight increase. The highest abundance of mangrove snails is found at station II and the lowest abundance is at stations I and III. The size of the mangrove snail in terms of shell length at station I is longer than that of stations II and III and in terms of weight at station III is heavier than stations I and station II. The quality of the waters refers to Government Regulation no. 22 of 2021 attachment VIII for marine life that still supports the life of mangrove snails.